Carnosol, a Natural Polyphenol, Inhibits Migration, Metastasis, and Tumor Growth of Breast Cancer via a ROS-Dependent Proteasome Degradation of STAT3 - Alsamri, Halima; El Hasasna, Hussain; Al Dhaheri, Yusra; Eid, Ali H.; Attoub, Samir; Iratni, Rabah (Frontiers in Oncology, 2019)
We have previously demonstrated that carnosol, a natural compound, inhibited in vitro cell viability and colony growth, induced cell cycle arrest, autophagy and apoptosis in human triple negative breast cancer (TNBC) cells. In the present study, we evaluated the ability of carnosol to inhibit tumor growth and metastasis in vivo. We found that non-cytotoxic concentrations of carnosol inhibited the migration and the invasion of MDA-MB-231 cells in wound healing and matrigel invasion assays. Gelatin zymography, ELISA, and RT-PCR assay revealed that carnosol inhibited the activity and downregulation the expression of MMP-9. Mechanistically, we demonstrated that carnosol suppressed the activation of STAT3 signaling pathway through a ROS-dependent targeting of STAT3 protein to proteasome-degradation in breast cancer (MDA-MB-231, Hs578T, MCF-7 and T47D) but not in colon cancer cells. We show that blockade of proteasome activity, by MG-132 and bortezomib, and ROS accumulation, by N-acetylcysteine, restored the level of STAT3 protein. In addition, using chick embryo tumor growth assay, we showed that carnosol significantly and markedly suppressed, in vivo, tumor growth and metastasis of breast cancer xenografts. To the best of our knowledge, we show for the first time that carnosol specifically target STAT3 for proteasome degradation in breast cancer. Our study further provide evidence that carnosol may represent a promising therapeutic candidate that modulate breast cancer growth and metastasis.